2020
DOI: 10.1021/acsbiomaterials.9b01019
|View full text |Cite
|
Sign up to set email alerts
|

Sensors and Psychomotor Metrics: A Unique Opportunity to Close the Gap on Surgical Processes and Outcomes

Abstract: The surgical process remains elusive to many. This paper presents two independent empirical investigations where psychomotor skill metrics were used to quantify elements of the surgical process in a procedural context during surgical tasks in a simulated environment. The overarching goal of both investigations was to address the following hypothesis: Basic motion metrics can be used to quantify specific aspects of the surgical process including instrument autonomy, psychomotor efficiency, procedural readiness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…In the current literature, motion metrics are mostly reported (90%) in the context of laparoscopic surgery and virtual reality rather than open surgery (10%). The most commonly explored motion metrics are time, path length, and velocity, while other metrics, like idle time, remain underdeveloped 17 . Our team sought to further investigate and provide valid evidence for idle time as a potential assessment metric of interest.…”
Section: Combining Motion Sensor With Video Data For Basic and Operative Procedural Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, motion metrics are mostly reported (90%) in the context of laparoscopic surgery and virtual reality rather than open surgery (10%). The most commonly explored motion metrics are time, path length, and velocity, while other metrics, like idle time, remain underdeveloped 17 . Our team sought to further investigate and provide valid evidence for idle time as a potential assessment metric of interest.…”
Section: Combining Motion Sensor With Video Data For Basic and Operative Procedural Skillsmentioning
confidence: 99%
“…The study design was an empirical assessment and comparison of participant procedure outcomes (standardized FPS) and performance metrics (motion, checklist). The participants ( n = 139) included residents from several Midwest surgical training programs and were part of a multi‐year study that included other simulators 17,25 . An overview of the LVH repair procedure steps is outlined in Table 2 and includes varying critical points.…”
Section: The “Error‐enabled” Laparoscopic Ventral Hernia (Lvh) Repair Simulatormentioning
confidence: 99%
“…While the use of objective and standardized assessments of resident competence may mitigate these concerns, routine use of such tools remains limited. Incorporating innovative strategies, such as video review or automated measures of psychomotor skill using motion tracking or virtual reality, into milestones assessments may help deemphasize bias based on individual trainee characteristics. Furthermore, the introduction of entrustable professional activities, which are actively being established by the American Board of Surgery, may improve the validity of resident assessment .…”
mentioning
confidence: 99%
“…Biomedical sensors are mostly used to detect patient samples or monitor organ activities in clinical settings. However, Mohamadipanah and co-workers contributed a paper to show that sensors can be applied to evaluate the skills of surgical trainees . They secured electromagnetic motion tracking sensors on trainees’ fingers and wrists for studying motion metrics.…”
mentioning
confidence: 99%
“…However, Mohamadipanah and co-workers contributed a paper to show that sensors can be applied to evaluate the skills of surgical trainees. 13 They secured electromagnetic motion tracking sensors on trainees' fingers and wrists for studying motion metrics. Their study suggested that instrument autonomy is correlated to psychomotor efficiency and that performance in virtual reality is correlated to clinical errors.…”
mentioning
confidence: 99%